(untitled) (Journal of Engineering, 2011)
E-learning comprises all forms of electronically supported teaching and learning. The information and communication system, whether networked or not, serve as specific media to implement the learning process; Computer based learning is one of the applications and processes of E-learning, sometimes abbreviated to CBL, refers to the use of computers as a key component of the educational environment [2]. Through my teaching, I found that there is a need for software learning packages at the lab to help students understand their courses especially in the subjects that need imagination like data structure. This research presents a data structure learning package for array and linear structure. Linear structure covers non-linked structure (stack and queue) and linked structure with their kinds.Through out this project the students can obtain a demonstration of how data structure is represented in memory. Most of the windows consist of three tabs, the first one is the information tab which contains all the information about the structures. The second tab contains all the operations performed on it and there is an ability to display all the operations in one executable program (full program), which receives inputs from the students, the students can enter different inputs according to the choices displayed and produce output after implementing by C++ program. The third tab contains exercises for the students to test their ability in understanding and after completing all the questions the package gives a score depending upon solutions. The package includes pictures and demos (movies) that represent the data structure implemented with 3D Max, finally all the windows are supplied with voice (my voice) to teach the students how to use the package.